A water-based bio-based anti-wear agent for water-based coating ink and preparation method thereof
By using aqueous bio-based anti-wear agents in aqueous coating inks, combined with the synergistic effect of palm wax, rice bran wax, oleic acid amide and nanocellulose whiskers with modified carbon fibers, the adverse effects of existing anti-wear agents on the environment and insufficient wear resistance are solved, and more efficient anti-wear effect and longer service life are achieved.
Patent Information
- Application Number
- CN202411793670.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The production and use of existing antiwear agents have adverse effects on the environment, and the wear resistance needs to be further improved.
Aqueous bio-based anti-wear agents, including palma wax, rice bran wax, oleic acid amide and nanocellulose whiskers and modified carbon fibers, are used as reinforcers to form an efficient anti-wear film through synergistic action.
Improves the wear resistance of water-based coatings and inks, extends service life, and reduces the impact on the environment.
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating and ink additives, and more specifically, to an aqueous bio-based anti-wear agent for aqueous coating and ink and a preparation method thereof. Background Art
[0002] Antiwear agents are chemical additives that can improve the wear resistance of coatings and inks. Antiwear agents usually form a thin film on the surface of the coating, reducing the direct contact between the coating formed by water-based coatings or inks and the outside world, thereby reducing the occurrence of wear and scratches. Antiwear agents can also increase the hardness and toughness of the coating or printed matter, further improving its wear resistance, thereby effectively reducing the damage to the coating or printed matter when it is rubbed, scratched or worn, thereby extending its service life and maintaining the integrity of its appearance.
[0003] The main component of commonly used anti-wear agents is polytetrafluoroethylene micropowder wax, which has excellent chemical stability, corrosion resistance, sealing, high lubricity and non-stickiness, electrical insulation and good anti-aging resistance. However, the main source of polytetrafluoroethylene is petroleum, which is made from raw materials extracted from petroleum cracking products through polymerization reaction. Its production and use process has a great adverse impact on the environment. Summary of the invention
[0004] In order to improve the environmental friendliness of the anti-wear agent, the present application provides an aqueous bio-based anti-wear agent for aqueous coating ink and a preparation method thereof.
[0005] In the first aspect, the present application provides a water-based bio-based anti-wear agent for water-based coating inks, using the following technical solution:
[0006] A water-based bio-based anti-wear agent for water-based coating ink comprises the following raw materials in parts by weight: 30-50 parts of palm wax, 16-24 parts of rice bran wax, 2-8 parts of oleic acid amide, and 0.2-0.6 parts of an enhancer.
[0007] By adopting the above technical scheme, palm wax and rice bran wax are both natural plant waxes, which are waxy substances extracted from palm leaves and rice bran of rice. They are derived from renewable resources and have good water resistance and wear resistance. They can be used as anti-wear agents to form a film with a lubricating effect, thereby improving the anti-wear properties of water-based coatings and inks. Oleic acid amide has a good lubricating effect and can further improve the anti-wear properties of the anti-wear agent. There is a synergistic effect among palm wax, rice bran wax and oleic acid amide, and the formed film has better anti-wear properties. The enhancer can improve the mechanical properties of the anti-wear agent, thereby increasing the service life of the anti-wear agent, thereby improving the anti-wear properties of the anti-wear agent.
[0008] Preferably, the reinforcing agent comprises nanocellulose whiskers and modified carbon fibers.
[0009] By adopting the above technical scheme, nanocellulose whiskers have good physical and chemical properties, are renewable, and have abundant sources. They can effectively improve the mechanical properties and strength of the anti-wear agent. Carbon fiber has excellent mechanical properties. Adding carbon fiber to the reinforcing agent can effectively improve the strength and mechanical properties of the anti-wear agent, thereby extending the service life of the anti-wear agent. Nanocellulose whiskers and modified carbon fibers work together to further improve the strength and wear resistance of the anti-wear agent.
[0010] Preferably, the mass ratio of the nanocellulose whiskers to the modified carbon fibers is (1.23-1.64):(1.71-2.01).
[0011] By adopting the above technical solution and controlling the mass ratio of nanocellulose whiskers to modified carbon fibers, the synergistic effect between the nanocellulose whiskers and the modified carbon fibers can be effectively improved, thereby improving the reinforcing effect of the reinforcing agent on the anti-wear agent.
[0012] Preferably, the method for preparing the modified carbon fiber comprises the following steps: adding polyacrylonitrile to N,N-dimethylformamide, heating to dissolve the polyacrylonitrile, magnetically stirring to obtain a spinning solution, adding a modifier to the spinning solution, ultrasonically dispersing for 20-25 minutes to obtain a modified spinning solution, electrospinning the modified spinning solution to obtain modified polyacrylonitrile fiber, and then pre-oxidizing and carbonizing to obtain a modified carbon fiber.
[0013] By adopting the above technical solution, by adding the modifier to the spinning solution, the polyacrylonitrile fiber obtained by spinning is uniformly distributed with the modifier, and the modifier can enhance the strength and mechanical properties of the modified carbon fiber.
[0014] Preferably, the receiving distance of the electrospinning is 13-15 cm, the extrusion rate is 0.5-0.6 mL / h, and the spinning voltage is 16-18 kV.
[0015] By adopting the above technical solution, by controlling the receiving distance, extrusion rate and spinning voltage of electrospinning, the growth morphology and size of carbon fiber can be effectively controlled, so that the prepared modified carbon fiber has good morphology and mechanical properties.
[0016] Preferably, the modifier is dendrite-shaped silica powder.
[0017] By adopting the above technical scheme, the dendrite-shaped silica powder has good mechanical properties and strength, and can effectively improve the mechanical properties and wear resistance of the modified carbon fiber. At the same time, the dendrite-shaped silica powder is mobile and can move to a certain extent when subjected to friction, thereby further reducing the surface friction coefficient and improving the wear resistance of the anti-wear agent.
[0018] Preferably, the concentration of polyacrylonitrile in the spinning solution is 12-14 wt %, and the amount of the modifier added is 1.24-2.38 wt % of the polyacrylonitrile.
[0019] By adopting the above technical scheme, the concentration of polyacrylonitrile and the amount of modifier added are controlled so that the morphology of the obtained carbon fiber is optimal. At the same time, the modifier has good dispersibility in the spinning solution, so that the branch-like silica can be evenly distributed in the modified carbon fiber, thereby effectively improving the mechanical properties and wear resistance of the modified carbon fiber.
[0020] In a second aspect, the present application provides a method for preparing an aqueous bio-based anti-wear agent for aqueous coating inks, using the following technical solution:
[0021] A method for preparing a water-based bio-based anti-wear agent for water-based coating ink comprises the following steps: mixing palm wax and oleic acid amide, heating to 70-80°C, stirring at a speed of 3000-3500 r / min for 10-15 min, adding a reinforcing agent, mixing at 3200-3500 r / min for 12-16 min, adding rice bran wax, mixing at 5000-5500 r / min for 20-30 min, cooling to complete solidification, crushing and ball milling to a particle size of 3-5 μm, and preparing the water-based bio-based anti-wear agent.
[0022] By adopting the above technical scheme, palm wax and oleamide are mixed, and then a reinforcing agent is added and stirred to make the reinforcing agent evenly dispersed. Then, rice bran wax is added and mixed evenly, and then the particle size is reduced by ball milling to obtain a water-based bio-based anti-wear agent. The water-based bio-based anti-wear agent has good dispersibility in ink and can provide good anti-wear performance for coatings and inks.
[0023] In summary, this application has the following beneficial effects:
[0024] 1. Since the present application adopts palm wax, rice bran wax and oleic acid amide, palm wax and rice bran wax are both natural plant waxes, which are waxy substances extracted from palm leaves and rice bran of rice. They are renewable resources and have good water resistance and wear resistance. They can be used as anti-wear agents to form a film with lubricating effect, thereby improving the anti-wear properties of water-based coatings and inks. Oleic acid amide has a good lubricating effect and can further improve the anti-wear properties of anti-wear agents. There is a synergistic effect among palm wax, rice bran wax and oleic acid amide, and the formed film has better anti-wear properties.
[0025] 2. In the present application, nanocellulose whiskers and modified carbon fibers are preferably used as reinforcing agents. Nanocellulose whiskers have good physical and chemical properties, are renewable, and have abundant sources. They can effectively improve the mechanical properties and strength of the antiwear agent. Carbon fibers have excellent mechanical properties. Adding carbon fibers to the reinforcing agent can effectively improve the strength and mechanical properties of the antiwear agent, thereby extending the service life of the antiwear agent. Nanocellulose whiskers and modified carbon fibers work together to further improve the strength and wear resistance of the antiwear agent.
[0026] 3. The present application adopts branch-shaped silica powder as a modifier. The branch-shaped silica powder has good mechanical properties and strength, and can effectively improve the mechanical properties and wear resistance of the modified carbon fiber. At the same time, the branch-shaped silica powder is mobile and can move to a certain extent when rubbed, thereby further reducing the surface friction coefficient and improving the wear resistance of the anti-wear agent. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to the embodiments.
[0028] Preparation Example 1 of bud-shaped silicon dioxide powder
[0029] Preparation Example 1
[0030] 14 mL of polyvinyl pyrrolidone was mixed with 160 mL of n-pentanol, and ultrasonicated for 2 h. 16 mL of ethanol and 4.5 mL of deionized water were added and mixed evenly. Then, 1.5 mL of 0.2 mol / L sodium citrate dihydrate aqueous solution was added and mixed evenly. Then, 3 mL of ammonia water was added and allowed to stand. Then, 1.5 mL of tetraethyl orthosilicate was added and mixed evenly. The mixture was reacted in an oil bath environment at 90 ° C for 180 min. The mixture was filtered using a polytetrafluoroethylene membrane, washed and dried to obtain linear silica.
[0031] 1.2 g of linear silica, 12 mL of ethanol and 4 mL of deionized water were mixed, 0.13 g of dopamine hydrochloride was added, the pH was adjusted to 8.5 with trishydroxymethylaminomethane, 1.2 mL of ethyl orthosilicate was added, and the mixture was allowed to stand in an oil bath at 30°C for 24 h. The mixture was filtered with a polytetrafluoroethylene membrane, washed and dried to obtain dendrite-shaped silica powder.
[0032] Preparation Example 2-8 of Modified Carbon Fiber
[0033] Preparation Example 2
[0034] Polyacrylonitrile was added to N,N-dimethylformamide, heated to dissolve the polyacrylonitrile, and then magnetically stirred to obtain a spinning solution. A modifier was added to the spinning solution, and ultrasonic dispersion was performed for 20 minutes. The modifier was the branch-like silica powder prepared in Preparation Example 1 to obtain a modified spinning solution. The concentration of polyacrylonitrile in the modified spinning solution was 12wt%, and the amount of the modifier added was 1.24wt% of the polyacrylonitrile. The modified spinning solution was electrospun to obtain modified polyacrylonitrile fiber. The extrusion rate of electrospinning was 0.5mL / h, the receiving distance was 13cm, and the spinning voltage was 16kV. The modified polyacrylonitrile fiber was pre-oxidized and carbonized to obtain modified carbon fiber.
[0035] Preparation Example 3
[0036] Polyacrylonitrile was added to N,N-dimethylformamide, heated to dissolve the polyacrylonitrile, and then magnetically stirred to obtain a spinning solution. A modifier was added to the spinning solution, and ultrasonic dispersion was performed for 25 minutes. The modifier was the branch-like silica powder prepared in Preparation Example 1 to obtain a modified spinning solution. The concentration of polyacrylonitrile in the modified spinning solution was 14wt%, and the amount of the modifier added was 2.38wt% of the polyacrylonitrile. The modified spinning solution was electrospun to obtain modified polyacrylonitrile fiber. The extrusion rate of electrospinning was 0.6mL / h, the receiving distance was 15cm, and the spinning voltage was 18kV. The modified polyacrylonitrile fiber was pre-oxidized and carbonized to obtain modified carbon fiber.
[0037] Preparation Example 4
[0038] The difference between Preparation Example 4 and Preparation Example 2 is that in Preparation Example 4, the concentration of polyacrylonitrile in the modified spinning solution is 8 wt %.
[0039] Preparation Example 5
[0040] The difference between Preparation Example 5 and Preparation Example 2 is that in Preparation Example 5, the concentration of polyacrylonitrile in the modified spinning solution is 15 wt %.
[0041] Preparation Example 6
[0042] The difference between Preparation Example 6 and Preparation Example 2 is that in Preparation Example 6, the amount of the modifier added is 0.67 wt % of polyacrylonitrile.
[0043] Preparation Example 7
[0044] The difference between Preparation Example 7 and Preparation Example 2 is that in Preparation Example 7, the amount of the modifier added is 5 wt % of polyacrylonitrile.
[0045] Preparation Example 8
[0046] The difference between Preparation Example 8 and Preparation Example 2 is that in Preparation Example 8, no modifier is added to the spinning solution. Example
[0047] Example 1
[0048] A water-based bio-based anti-wear agent for water-based coatings and inks, comprising the following raw materials in parts by weight: 30 kg of palm wax, 16 kg of rice bran wax, 2 kg of oleic acid amide, and 0.2 kg of a reinforcing agent, wherein the reinforcing agent comprises nanocellulose whiskers and modified carbon fibers in a mass ratio of 1.23:1.71, wherein the modified carbon fibers are the modified carbon fibers obtained in Preparation Example 2, and the nanocellulose whiskers are selected from Zhongke Leiming (Beijing) Technology Co., Ltd., model CNWs-50.
[0049] The method for preparing the water-based bio-based anti-wear agent for water-based coating ink comprises the following steps:
[0050] Palm wax and oleic acid amide were mixed, heated to 70°C, stirred at 3000 r / min for 15 min, then a reinforcing agent was added, mixed at 3200 r / min for 16 min, and then rice bran wax was added, mixed at 5000 r / min for 30 min. After cooling until completely solidified, the mixture was crushed and ball-milled to a particle size of 3 μm to obtain a water-based bio-based anti-wear agent.
[0051] Example 2
[0052] A water-based bio-based anti-wear agent for water-based coatings and inks, comprising the following raw materials in parts by weight: 50 kg of palm wax, 24 kg of rice bran wax, 8 kg of oleic acid amide, and 0.6 kg of a reinforcing agent, wherein the reinforcing agent comprises nano-cellulose whiskers and modified carbon fibers in a mass ratio of 1.64:2.01, wherein the modified carbon fibers are selected from the modified carbon fibers obtained in Preparation Example 3, and the nano-cellulose whiskers are selected from Zhongke Leiming (Beijing) Technology Co., Ltd., model CNWs-50.
[0053] The method for preparing the water-based bio-based anti-wear agent for water-based coating ink comprises the following steps:
[0054] Palm wax and oleic acid amide were mixed, heated to 80°C, stirred at 3500 r / min for 10 min, then a reinforcing agent was added, mixed at 3500 r / min for 12 min, and then rice bran wax was added, mixed at 5500 r / min for 20 min. After cooling until completely solidified, the mixture was crushed and ball-milled to a particle size of 5 μm to obtain a water-based bio-based anti-wear agent.
[0055] Example 3
[0056] The difference between Example 3 and Example 1 is that in Example 3, the modified carbon fiber is the modified carbon fiber prepared in Preparation Example 4.
[0057] Example 4
[0058] The difference between Example 4 and Example 1 is that in Example 4, the modified carbon fiber is the modified carbon fiber prepared in Preparation Example 5.
[0059] Example 5
[0060] The difference between Example 5 and Example 1 is that in Example 5, the modified carbon fiber is the modified carbon fiber prepared in Preparation Example 6.
[0061] Example 6
[0062] The difference between Example 6 and Example 1 is that in Example 6, the modified carbon fiber is the modified carbon fiber prepared in Preparation Example 7.
[0063] Example 7
[0064] The difference between Example 7 and Example 1 is that in Example 7, the modified carbon fiber is the modified carbon fiber prepared in Preparation Example 8.
[0065] Example 8
[0066] The difference between Example 8 and Example 1 is that in Example 8, the reinforcing agent includes nanocellulose whiskers and modified carbon fibers in a mass ratio of 1.23:0.52.
[0067] Example 9
[0068] The difference between Example 9 and Example 1 is that in Example 9, the reinforcing agent includes nanocellulose whiskers and modified carbon fibers in a mass ratio of 1.23:2.78.
[0069] Comparative Example
[0070] Comparative Example 1
[0071] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, no reinforcing agent is added.
[0072] Comparative Example 2
[0073] The difference between Comparative Example 2 and Example 1 is that, in Comparative Example 2, the following raw materials are included: 25 kg palm wax, 30 kg rice bran wax, 7 kg oleic acid amide, and 0.4 kg enhancer.
[0074] Comparative Example 3
[0075] The difference between Comparative Example 3 and Example 1 is that, in Comparative Example 3, the following raw materials are included: 30 kg palm wax, 16 kg rice bran wax, 2 kg oleic acid amide, and 2 kg enhancer.
[0076] Comparative Example 4
[0077] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, the particle size of the aqueous bio-based anti-wear agent is 10 μm.
[0078] Comparative Example 5
[0079] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, the particle size of the aqueous bio-based anti-wear agent is 1 μm.
[0080] Detection Methods
[0081] According to the raw materials and preparation methods of Examples 1-9 and Comparative Examples 1-5, a water-based bio-based anti-wear agent was prepared, and the water-based bio-based anti-wear agent was used to prepare a water-based coating according to the following formula. The water-based coating includes the following raw materials: 45% water-based acrylic resin, 15% filler, 0.7% dispersant, 0.1% defoamer, 12% water-based bio-based anti-wear agent, and the balance water, wherein the dispersant is selected from German BYK Company, model DISPERBYK-154, the defoamer is selected from Digo Company, model Foamex 840, and the filler is mica powder.
[0082] At the same time, a blank case was set up. The blank case was a water-based coating without adding a water-based bio-based anti-wear agent. The water-based coating was prepared by using an equal amount of water to replace the water-based bio-based anti-wear agent. The prepared water-based coating was tested for wear resistance. The measurement method referred to GB / T 1768-2006 "Determination of abrasion resistance of paints and varnishes - Rotating rubber grinding wheel method", and the results were recorded in Table 1.
[0083] Table 1 Wear resistance of anti-wear agents
[0084] project Wear resistance / mg Example 1 1.02 Example 2 1.05 Example 3 1.98 Example 4 1.87 Example 5 2.21 Example 6 2.19 Example 7 2.01 Example 8 1.85 Example 9 1.79 Comparative Example 1 3.24 Comparative Example 2 3.56 Comparative Example 3 2.89 Comparative Example 4 2.97 Comparative Example 5 3.14 Blank example 5.01
[0085] According to Table 1, Examples 1-2 and the blank example, it can be seen that the wear resistance of Example 1-2 is better than that of the blank example. A water-based bio-based anti-wear agent is added to the water-based coating of Example 1-2, indicating that the water-based bio-based anti-wear agent can effectively improve the wear resistance of the water-based coating. The water-based bio-based anti-wear agent includes palm wax, rice bran wax, oleic acid amide and an enhancer. Palm wax and rice bran wax are natural plant waxes. Palm wax is a waxy substance extracted from palm leaves, while rice bran wax is a waxy substance extracted from rice bran of rice. Palm wax and rice bran wax are both renewable resources and have good water resistance and wear resistance. They can form a film with a lubricating effect, thereby improving the wear resistance of the water-based coating. Oleic acid amide has a good lubricating effect, which can further improve the wear resistance of the anti-wear agent. There is a synergistic effect among palm wax, rice bran wax and oleic acid amide, which can further improve the wear resistance of the water-based coating. The enhancer can improve the mechanical properties and strength of the coating, thereby improving the service life of the anti-wear agent, thereby improving the wear resistance of the anti-wear agent.
[0086] Compared with comparative examples 1-3, the wear resistance of embodiments 1-2 is better than that of comparative examples 1-3. No enhancer was added in comparative example 1, the addition amounts of palm wax, rice bran wax, oleic acid amide and enhancer were changed in comparative example 2, and the addition amount of enhancer was increased in comparative example 3, indicating that the addition of enhancer can improve the anti-wear effect of anti-wear agent, thereby improving the wear resistance of coating. At the same time, there is a synergistic effect between palm wax, rice bran wax and oleic acid amide. The weight parts disclosed in the present application can make the synergistic effect between palm wax, rice bran wax and oleic acid amide better, and the addition amount of enhancer will also affect the enhancing effect of enhancer on anti-wear agent.
[0087] The reinforcing agent is composed of nanocellulose whiskers and modified carbon fibers. Nanocellulose whiskers have good physical and chemical properties and can effectively improve the mechanical properties and strength of the anti-wear agent. The modified carbon fibers have excellent mechanical properties and can further improve the strength and mechanical properties of the anti-wear agent, thereby extending the service life of the anti-wear agent and improving the wear resistance of the coating in a more long-term and effective manner. At the same time, there is a synergistic effect between nanocellulose whiskers and modified carbon fibers, and the synergy between the two can further improve the strength and wear resistance of the anti-wear agent.
[0088] Compared with Example 4-5, the wear resistance of Example 4-5 is inferior to that of Example 1. Example 4-5 changes the particle size of the water-based bio-based anti-wear agent. In Example 4, the particle size of the water-based bio-based anti-ink agent is increased, which is easy to affect the leveling and roughness of the coating and is not easy to wetting. After the water-based bio-based anti-wear agent is added, the particle size is large, which is easy to affect the stability of the coating. In Example 5, the particle size of the water-based bio-based anti-wear agent is reduced, which makes the water-based bio-based anti-wear agent easy to agglomerate and reduce its dispersibility, thereby reducing the anti-wear effect of the water-based bio-based anti-wear agent and increasing the viscosity of the coating emulsion system, thereby affecting the use of the coating.
[0089] Compared with Example 1, the wear resistance of Example 3-4 is inferior to that of Example 1. When preparing the modified carbon fiber used in Example 3-4, the concentration of polyacrylonitrile in the modified spinning solution was adjusted, which shows that the concentration of polyacrylonitrile will affect the morphology and performance of the modified carbon fiber. The concentration of polyacrylonitrile in the spinning solution directly affects the morphology of the polyacrylonitrile fiber formed by spinning. If the concentration of polyacrylonitrile is too high or too low, there will be more rods in the polyacrylonitrile fiber, thereby making the morphology of the polyacrylonitrile fiber uneven. The modified carbon fiber obtained after carbonization has poor morphology and poor mechanical properties.
[0090] Compared with Example 1, the wear resistance of Example 5-6 is inferior to that of Example 1. When preparing the modified carbon fiber used in Example 5-6, the amount of modifier added was adjusted, which shows that the amount of modifier added will affect the morphology and mechanical properties of the modified carbon fiber. The modifier is a dendrite-like silica powder. The dendrite-like silica has a special dendrite-like structure. It has good mechanical properties and strength, and is mobile, which can effectively improve the mechanical properties and wear resistance of the modified carbon fiber. At the same time, the anti-wear agent can move to a certain extent when subjected to friction, thereby further reducing the friction coefficient of the surface and improving the wear resistance of the anti-wear agent. When the amount of modifier added is reduced, the content of dendrite-like silica is reduced, which reduces the reinforcing effect of the modifier on the modified carbon fiber. When the amount of modifier added is increased, the distribution of dendrite-like silica in the modified spinning solution is uneven, which makes it easy for the modifier to be unable to be evenly dispersed in the modified carbon fiber, thereby reducing the improvement of the wear resistance of the anti-wear agent by the reinforcing agent.
[0091] Compared with Example 1, the wear resistance of Example 7 is inferior to that of Example 1. No modifier was added during the preparation of the modified carbon fiber used in Example 7, which shows that the addition of the modifier can effectively improve the performance of the anti-wear agent, thereby improving the wear resistance of the coating. The modifier is dendrite-shaped silica, which has a special dendrite-shaped structure and good strength, thereby improving the mechanical properties and strength of the modified carbon fiber, thereby improving the mechanical properties and strength of the anti-wear agent.
[0092] Compared with Example 1, the wear resistance of Example 8-9 is inferior to that of Example 1. Example 8-9 adjusts the mass ratio of nanocellulose whiskers to modified carbon fibers in the reinforcing agent, indicating that the mass ratio of nanocellulose whiskers to modified carbon fibers will affect the wear resistance of the anti-wear agent. Both nanocellulose whiskers and modified carbon fibers have fibrous structures. When the two are used together, the nanocellulose whiskers and modified carbon fibers are entangled with each other to form a reinforced network, thereby improving the strength and wear resistance of the anti-wear agent, making the anti-wear agent less likely to be damaged or separated from the coating, thereby enhancing the service life of the anti-wear agent and further improving the wear resistance of the coating. When the mass ratio between nanocellulose whiskers and modified carbon fibers changes, the synergistic effect of nanocellulose whiskers and modified carbon fibers decreases, thereby reducing the effect of the anti-wear agent.
[0093] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A water-based bio-based anti-wear agent for water-based coatings and inks, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of palm wax, 16-24 parts of rice bran wax, 2-8 parts of oleic acid amide, and 0.2-0.6 parts of a reinforcing agent, wherein the particle size of the water-based bio-based anti-wear agent is 3-5 μm; The reinforcing agent comprises nanocellulose whiskers and modified carbon fibers. The preparation method of the modified carbon fibers comprises the following steps: adding polyacrylonitrile to N,N-dimethylformamide, heating to dissolve the polyacrylonitrile, magnetically stirring to obtain a spinning solution, adding a modifier to the spinning solution, ultrasonically dispersing for 20-25 minutes to obtain a modified spinning solution, electrostatically spinning the modified spinning solution to obtain modified polyacrylonitrile fibers, and then pre-oxidizing and carbonizing to obtain modified carbon fibers. The modifier is a dendrite-shaped silicon dioxide powder.
2. The aqueous bio-based anti-wear agent for aqueous coating ink according to claim 1, characterized in that: The mass ratio of the nanocellulose whiskers to the modified carbon fibers is (1.23-1.64):(1.71-2.01).
3. The aqueous bio-based anti-wear agent for aqueous coating ink according to claim 1, characterized in that: The receiving distance of the electrospinning is 13-15 cm, the extrusion rate is 0.5-0.6 mL / h, and the spinning voltage is 16-18 kV.
4. The aqueous bio-based anti-wear agent for aqueous coatings and inks according to claim 1, characterized in that: The concentration of polyacrylonitrile in the spinning solution is 12-14 wt %, and the amount of the modifier added is 1.24-2.38 wt % of the polyacrylonitrile.
5. The method for preparing the water-based bio-based anti-wear agent for water-based coating ink according to any one of claims 1 to 4, characterized in that: The following steps are involved: Palm wax and oleic acid amide are mixed, heated to 70-80°C, stirred at 3000-3500 r / min for 10-15 minutes, a reinforcing agent is added, mixed at 3200-3500 r / min for 12-16 minutes, rice bran wax is added, mixed at 5000-5500 r / min for 20-30 minutes, cooled to completely solidified, crushed and ball-milled to obtain a water-based bio-based anti-wear agent.
Citation Information
Patent Citations
Water-based smooth high-wear-resistance gloss oil as well as preparation method and application thereof
CN117683402A
Wear-resistant polyurethane and preparation method thereof
CN118755254A